Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.18632/oncotarget.3187
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier permeability of gefitinib in patients with brain metastases from non-small-cell lung cancer before and during whole brain radiation therapy

Abstract: IntroductionTo explore the ability of gefitinib to penetrate blood brain barrier (BBB) during whole brain radiation therapy (WBRT).Patients and MethodsEnrolled in this study were eligible patients who were diagnosed with BM from NSCLC. Gefitinib was given at 250 mg/day for 30 days, then concurrently with WBRT (40 Gy/20 F/4 w), followed by maintenance. Serial CSF and blood samples were collected on 30 day after gefitinib administration, and at the time of 10, 20, 30 and 40 Gy following WBRT. CSF and plasma samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 41 publications
(52 reference statements)
1
64
2
Order By: Relevance
“…EGFR-TKIs, which are small molecular inhibitors of the EGFR pathway, have been proven much more effective than cisplatinbased chemotherapy in the progression-free survival of NSCLC patients (24). WBRT can also increase the bloodbrain barrier permeability of gefitinib (11). Therefore, EGFR-TKIs are effective in the management of NSCLC patients with brain metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR-TKIs, which are small molecular inhibitors of the EGFR pathway, have been proven much more effective than cisplatinbased chemotherapy in the progression-free survival of NSCLC patients (24). WBRT can also increase the bloodbrain barrier permeability of gefitinib (11). Therefore, EGFR-TKIs are effective in the management of NSCLC patients with brain metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant use of WBRT and gefitinib is well tolerated with a median OS time of 12.0 to 15.4 months (10,11). Some studies reported that the blood-brain barrier permeability of EGFR-TKIs could be increased in accordance with the escalated dose of WBRT (11,12). The cerebrospinal fluid-to-plasma ratio of NSCLC patients with brain metastasis reaches its peak (1.87%±0.72%) at a WBRT dose of 30 Gy (11).…”
Section: Introductionmentioning
confidence: 99%
“…Patients can often develop CNS metastases during treatment, even when their extracranial tumors are still under control (31). CNS concentrations of all currently available agents are lower than plasma [gefitinib has a CSF concentration approximately 1% of serum and erlotinib has a CSF concentration 5% of serum (32,33)]. Many EGFR TKIs that have been designed for improved CNS penetration are currently under investigation.…”
Section: Pharmacodynamic Limitationsmentioning
confidence: 99%
“…Potential mechanisms of synergism include cell cycle arrest, induction of apoptosis, inhibition of radiation-induced DNA repair mechanisms and increased EGFR expression in radioresistant clones (69)(70)(71). In addition, radiotherapy might disrupt the BBB, facilitating passage of drugs into the brain (72).…”
Section: Rationale and Clinical Datamentioning
confidence: 99%